A Salmonella enterica Surrogate for Future Validation Studies for Nonfat Dried Milk and Low-Moisture Food Environments - Kavita Patil; Manita Adhikari; Peter Rubinelli; Jennifer C. Acuff (Journal of Food Protection)
Low-moisture food persistent bacterial populations (LMF PBPs) may be responsible for pathogen harborage in LMF processing environments, resulting in outbreaks and recalls. To address this issue, industry requires a surrogate to understand the survivability of LMF PBP and perform in-plant validation studies to reduce the level of this pathogen to an acceptable level. Hygienic controls for the LMF industry must be tailored to different equipment, environments, and food types. In-plant validations with a surrogate would assist with evaluating the efficacy of sanitation protocols that eliminate LMF PBPs and harborage. This study explored surrogates for Salmonella LMF PBP to provide tools for challenge studies to eliminate LMF PBPs from stainless-steel surfaces. Three surrogates (Escherichia coli MP 26, Enterococcus faecium, Pediococcus acidilactici) were evaluated for similarity to a Salmonella LMF PBP in nonfat dried milk (NFDM) formed on stainless steel coupons stored at 30% or 70% relative humidity (RH) at 25 °C. Coupons were prepared with a previously established method to form an LMF PBP (0.5 g of NFDM, 0.4 mL culture). Microbial survival was enumerated at intervals (0, 1, 3, 5, and 7 days) using standard plating techniques. An ANOVA and Tukey’s HSD tests were used to compare log reductions to identify suitable surrogates. E. faecium exhibited higher survival trends that were most similar to Salmonella, with no significant differences in log reductions (p > 0.05). In contrast, E. coli surrogate panel and P. acidilactici showed significantly greater reductions, making them unsuitable surrogate candidates for Salmonella. Matrices and RH interactions influenced survival, but E. faecium consistently mirrored Salmonella behavior. E. faecium was similar but hardier than Salmonella LMF PBPs and could be used in processing environments for challenging and validating sanitation protocols.